SGID: a comprehensive and interactive database of the silkworm. (14th December 2019) - Zhu, Zhenglin; Guan, Zhufen; Liu, Gexin; Wang, Yawang; Zhang, Ze
Abstract: Although the domestic silkworm ( Bombyx mori ) is an important model and economic animal, there is a lack of comprehensive database for this organism. Here, we developed the silkworm genome informatics database (SGID). It aims to bring together all silkworm-related biological data and provide an interactive platform for gene inquiry and analysis. The function annotation in SGID is thorough and covers 98% of the silkworm genes. The annotation details include function description, Gene Ontology, Kyoto Encyclopedia of Genes and Genomes pathway, subcellular location, transmembrane topology, protein secondary/tertiary structure, homologous group and transcription factor. SGID provides genome-scale visualization of population genetics test results based on high-depth resequencing data of 158 silkworm samples. It also provides interactive analysis tools of transcriptomic and epigenomic data from 79 NCBI BioProjects. SGID will be extremely useful to silkworm research in the future.